1985
DOI: 10.1002/ana.410180415
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia masquerading as cerebrovascular disease (hypoglycemic hemiplegia)

Abstract: Hypoglycemia produced hemiplegia with right-sided predilection in 16 patients initially suspected of having suffered a stroke. Fifteen patients had no demonstrable brain disease, and the hemiplegia cleared rapidly once the hypoglycemia was corrected. Invasive investigations such as carotid arteriography are not required in most patients. The features of hypoglycemia hemiplegia suggest that a selective neuronal vulnerability and not underlying focal brain disease is responsible in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(27 citation statements)
references
References 9 publications
0
25
0
2
Order By: Relevance
“…Hypoglycemia purposely induced by insulin infusion, undertaken in an attempt to reproduce HH, has unpredictably resulted in hemiplegia. 3 Based on 29 well-documented cases from the literature, the clinical spectrum of HH is outlined in Table 1. 3 -" 13 -15 HH usually occurs in diabetic patients receiving insulin (72%) or oral hypoglycemic agents (14%), but HH also occurs in nondiabetic patients with other causes of hypoglycemia (14%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoglycemia purposely induced by insulin infusion, undertaken in an attempt to reproduce HH, has unpredictably resulted in hemiplegia. 3 Based on 29 well-documented cases from the literature, the clinical spectrum of HH is outlined in Table 1. 3 -" 13 -15 HH usually occurs in diabetic patients receiving insulin (72%) or oral hypoglycemic agents (14%), but HH also occurs in nondiabetic patients with other causes of hypoglycemia (14%).…”
Section: Discussionmentioning
confidence: 99%
“…12 Yet in certain patients, hypoglycemia presents with isolated, focal neurologic signs. 3 " 10 In these patients, the diagnosis is not readily apparent, leading to unnecessary evaluation for cerebrovascular disease. Two such cases are reported.…”
mentioning
confidence: 99%
“…reviewed 16 patients presenting with weakness and blood glucose of less than 45 mg/dl. 54 Most patients were initially misdiagnosed as stroke, all but one were conscious during the attack, four had associated aphasia, most (12/16) had right sided weakness and all had resolution without recurrence within 15 minutes of glucose infusion. One of the www.intechopen.com patients had a total of four episodes of transient hemiplegia before hypoglycemia was diagnosed.…”
Section: Hypoglycemic Hemiplegiamentioning
confidence: 97%
“…Autopsy of this patient showed diffuse cortical injury, but no focal lesions. 54 Another review involving 29 patients found 72% were caused by insulin treatment, and mean serum glucose was 35 mg/dL. Most (78%) had recurrent attacks, and on average 3.5 attacks occurred before a diagnosis of hypoglycemic hemiparesis was made.…”
Section: Hypoglycemic Hemiplegiamentioning
confidence: 99%
See 1 more Smart Citation